Proceedings of the workshop semigroups and languages (World Scientific, 2004)
This book provides introductory accounts of recent research in rational languages and their connections with finite semigroups, including the celebrated BG=PG theorem, infinite languages, free profinite monoids and their applications to pseudovarieties, parallel complexity classes related to automata, semigroups and logic, algebraic monoids, geometric methods in semigroup presentations, automatic groups and groups acting on -trees. There is also an extensive survey of algorithmic problems in groups, semigroups and inverse monoids